Metabolism of orally administered tauroursodeoxycholic acid in patients with primary biliary cirrhosis. Issue 3 (March 1996) - Setchell, K D; Rodrigues, C M; Podda, M; Crosignani, A
Abstract : The metabolism of tauroursodeoxycholic acid orally administered and its effects on the bile acid pool of patients with asymptomatic/mildly symptomatic primary biliary cirrhosis is described. Patients were randomly assigned 500, 1000, or 1500 mg/day of tauroursodeoxycholate for six months. Biliary and serum bile acids were measured before and during treatment by gas chromatography-mass spectrometry and by high performance liquid chromatography. During tauroursodeoxycholate administration, the proportion of total ursodeoxycholate in bile reached mean (SEM) 34.4 (4.5)%, 32.8 (2.8)%, and 41.6 (3.0)% with doses of 500, 1000, and 1500 mg/day, respectively. Significant decreases in the proportions of chenodeoxycholate and cholate resulted. The glycine/taurine ratio of the biliary bile acid pool decreased from 1.9 at baseline, to 1.1 with the highest dose. Ursodeoxycholate in bile was conjugated with glycine and taurine, indicating that tauroursodeoxycholate undergoes significant deconjugation and reconjugation during its enterohepatic recycling. The proportion of lithocholate in bile remained unchanged. Fasting serum conjugated ursodeoxycholate concentration positively correlated with the tauroursodeoxycholate dose, and the increased proportion of ursodeoxycholate was accompanied by substantial decreases in the endogenous bile acids. Compared with previously published data for ursodeoxycholic acid therapy, these findings indicate that the shift toward a more hydrophilic bile acid pool is greater and potentially more favourable with tauroursodeoxycholate, and this is because of the reduced intestinal biotransformation of tauroursodeoxycholate.